2016
DOI: 10.15434/kssh.2016.29.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Attempts to Quit Smoking in Korean Adolescents

Abstract: This study investigated the rate of attempts to quit smoking and related factors in Korean adolescent smokers. Methods: The findings of this study were based on the data obtained from the '2015 11 th Korea Youth Risk Behavior Web-based Survey'. The number of subjects was 5,123. Results: 71.7% of adolescent smokers in our study group had made previous attempts to quit smoking. Logistic regression analysis showed that the following significant factors were related to attempts to quit smoking: smoking amount (OR=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Of the social factors, having viewed an anti-smoking advertisement, having participated in school-based anti-smoking programs, having experienced passive smoking at school and in public places, having a close friend who currently smoked, and high perceived family socioeconomic status were positively associated with smoking cessation attempts. Regarding having viewed anti-smoking advertisements, the results from this study support previous research on Korean adolescent smokers, which found that anti-smoking advertisements significantly increased smoking cessation attempts [15]. Yim and Park [9] reported that exposure to anti-smoking advertisements was positively related to smoking cessation attempts, with a stronger relationship observed among light than heavy (more than 10 cigarettes per day) adolescent smokers.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Of the social factors, having viewed an anti-smoking advertisement, having participated in school-based anti-smoking programs, having experienced passive smoking at school and in public places, having a close friend who currently smoked, and high perceived family socioeconomic status were positively associated with smoking cessation attempts. Regarding having viewed anti-smoking advertisements, the results from this study support previous research on Korean adolescent smokers, which found that anti-smoking advertisements significantly increased smoking cessation attempts [15]. Yim and Park [9] reported that exposure to anti-smoking advertisements was positively related to smoking cessation attempts, with a stronger relationship observed among light than heavy (more than 10 cigarettes per day) adolescent smokers.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, students who participated in school-based anti-smoking programs were more likely to quit smoking. This result is supported by previous research showing that participation in school-based anti-smoking programs increased adolescents' smoking cessation attempts [10,15]. In particular, awareness of the short-term physical hazards of smoking from participating in school-based anti-smoking programs is known to further increase the strength of negative attitudes toward smoking [22].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations